Pengaruh Gaya Arsitektur Kolonial Belanda pada Gereja Katolik Santo Yusup Blitar - Palupi Titasari, Coleta; Dedy Prawirajaya R, Kadek; Ngene Ngiso, Vinsensia Quirina (Humanis, 2024)
Santo Yusup Blitar Catholic Church is a Dutch colonial heritage building, which was built in 1928 with the parish priest being Pastor A. Bastiaansen and assistant pastor Jan Wolter CM. The church building still survives today and has not undergone many architectural changes. This research discusses the characteristics of the Dutch colonial style which influenced the Santo Yusup Catholic Church in Blitar. The research was studied using descriptive methods to describe the characteristics of the Dutch colonial style which influenced the design style of the Santo Yusup Blitar Catholic Church. The aim of this research is to create a systematic, factual and accurate description, picture of the Santo Yusup Blitar Catholic Church. Data collection was carried out by interviews, literature study, field observation and documentation. Descriptive analysis method to analyze, describe and summarize various conditions and situations of the Santo Yusup Catholic Church. The results of the research show that the building components of the Santo Yusuf Blitar Catholic Church are classical European in style, influenced by the Dutch colonial design style.